2020
DOI: 10.1017/s1751731119003021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic hormones, grazing behaviour, offspring physical distance and productive response of beef cow grazing at two herbage allowances

Abstract: Herbage allowance (HA) management during gestation–lactation cycle of cows grazing native grasslands improves pregnancy rates and calves’ weaning weight records. Those improvements were associated with greater herbage mass, and better body condition score (BCS) and metabolic status of the cows, which could affect grazing and maternal behaviour, particularly when temporary suckling restriction (TSR) and flushing (FL) is applied. The objective of this study was to evaluate the effect of HA during the gestation–l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…High HA led to moderate improvements in cow BCS (0.5 units) and energy intake (11%) during autumn. BCS and IGF-I concentrations were greater during winter, which led to more cows ovulating early in the next breeding season and successfully increased the herd reproductive response (Claramunt et al, 2020). This set of experiments has shown how the energy flow can be efficiently used in producing beef by maximizing energy consumption by cows and improving the energy partitioning in the animals (Do Carmo et al, 2016).…”
Section: Managing Herbage Allowance and Cow Body Condition In Campos mentioning
confidence: 89%
See 1 more Smart Citation
“…High HA led to moderate improvements in cow BCS (0.5 units) and energy intake (11%) during autumn. BCS and IGF-I concentrations were greater during winter, which led to more cows ovulating early in the next breeding season and successfully increased the herd reproductive response (Claramunt et al, 2020). This set of experiments has shown how the energy flow can be efficiently used in producing beef by maximizing energy consumption by cows and improving the energy partitioning in the animals (Do Carmo et al, 2016).…”
Section: Managing Herbage Allowance and Cow Body Condition In Campos mentioning
confidence: 89%
“…The main strategy elaborated with and implemented by farmers was to increase standing biomass and forage production of the grasslands by managing the grassland-herd interaction, increasing herbage allowance (HA) and adjusting allocation of animal categories to different paddocks according to standing biomass. Associated with suckling restriction and flushing, HA management modified energy partitioning between production and reproduction, which increased the efficiency of cow energy use (Soca et al, 2013a,b;Do Carmo et al, 2016;Claramunt et al, 2017Claramunt et al, , 2020. Management of HA required variation of stocking rate and/or sheep-tocattle ratio at the paddock or system scale and monitoring of standing biomass.…”
Section: Improving Sustainability Of Uruguayan Family Farms Through Cmentioning
confidence: 99%
“…In cow-calf experiments, Claramunt et al (2018) and Do Carmo et al 2018evidenced that monthly adjustments of the stocking rates to achieve target forage offer levels are key to increased animal productivity. Several case studies also demonstrated that stocking rate management at farm scale increased livestock production via higher calf weaning weights, pregnancy rates, and increased profitability (Albicette et al, 2017;Do Carmo et al, 2019;Claramunt and Meikle, 2020).…”
Section: Stocking Rate Managementmentioning
confidence: 99%
“…These management tools could help us to ensure adequate levels of body condition score at calving, and therefore higher annual pregnancy rates (Quintans et al, 2010, Soca et al, 2013Do Carmo et al, 2018), and to increase calf weight when suckling restriction is combined with a high forage offer (Claramunt and Meikle, 2020). Most of these tools were developed from the conceptual model proposed by Soca and Orcasberro (1992) that combine indicators of pasture structure and the energy balance of grazing cows to guide the management decisions in Campos ecosystems.…”
Section: Nutritional Management Of Livestockmentioning
confidence: 99%